Perbedaan Pengetahuan dan Sikap Remaja Putri Sebelum dan Sesudah Diberikan Penyuluhan Tentang Berpacaran Sehat di SMA Negeri 1 Kuta Utara - Ni Putu Harista Diandari; Ni Gusti Kompiang Sriasih; Ni Luh Putu Sri Erawati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Adolescence is a transition period from child to adult. During this period, changes occur both physically and psychologically, especially in the bio-psycho-social aspects. Changes during this period result in teenagers starting to be attracted to the opposite sex which will refer to dating activities. Good dating is healthy dating. This research aims to provide education to teenagers about safe, healthy dating. This type of research is pre-experimental with a one group pretest posttest design which was carried out at SMA Negeri 1 North Kuta in April-May 2022. The sample was 75 respondents using a simple random sampling technique. The data collection process uses a questionnaire instrument. The research results showed that the mean value of the knowledge variable before counseling was 90, after counseling it was 96.7. The percentage of attitude values obtained before counseling was 45% positive attitudes and 55% negative attitudes. After counseling the percentage value of positive attitudes was 56% and negative attitudes 44%. Testing the normality of the data using the Kolmogorov-Smirnov test obtained a p value of 0.000 (p<0.005), the data was not normally distributed. The Wilcoxon test results for the knowledge variable have a p value of 0.000 and a Z value of -5.471, whereas for the attitude variable the p value is 0.000 and the Z value is -4.591. The results of this analysis show that there is an increase in knowledge before and after being given counseling and there are differences in attitudes before and after being given counseling, so it is hoped that providing counseling can increase teenagers' knowledge and attitudes about healthy dating.